Microstructure, piezoelectric properties and phase transition of (Pb 0.90Ba0.10)ZrO3 ceramics prepared by solid state reaction method - Bongkarn T. (2014)
(Pb0.90Ba0.10)ZrO3 was prepared via the solid state reaction method under various heat treatment conditions. Microstructure, piezoelectric properties and phase transitions of (Pb 0.90Ba0.10)ZrO3 were studied. Grain size of the samples is in the range of 0.5 to 1.3 μm. The d33 values of the samples are in the range of 19-27 pC/N while the planar coupling coefficient kp is about 0.3 for all samples. Antiferroelectric to ferroelectric phase transition was found in samples re-calcined at 850°C and sintered at 1325°C and 1350°C. However, ferroelectric-to-antiferroelectric phase transition was not detected. The ferroelectric-to-paraelectric transition temperature slightly increases as the sintering temperature increases. This can be related to the characteristics of the grains in the ceramics. © 2002 Taylor & Francis.